Understanding Physical Developer (PD): Part II – Is PD targeting eccrine constituents?. (December 2015) - de la Hunty, Mackenzie; Moret, Sébastien; Chadwick, Scott; Lennard, Chris; Spindler, Xanthe; Roux, Claude
Highlights: Investigation into the chemical targets of physical developer. Induced sweating shows increased physical developer reactivity at pore locations. Physical developer eccrine reactivity requires the presence of non-water soluble constituents. Physical developer may target a combination of eccrine and lipid constituents in fingermark residue. Abstract: Physical developer (PD) is a fingermark development technique that deposits silver onto fingermark ridges. It is the only technique currently in routine operational use that gives results on porous substrates that have been wet. There is a reasonable understanding of the working solution chemistry, but the chemical constituent(s) contained in fingermark residue that are specifically targeted by PD are largely unknown. A better understanding of the PD technique will permit a more informed selection of alternative or complementary detection methods, and greater usage in operational laboratories. Recent research by our group has shown that PD does not selectively target the lipids present in the residue. This research investigated the hypothesis that PD targets the eccrine constituents in fingermark residue. This was tested by comparison of PD and indanedione-zinc (Ind-Zn) treated natural fingermarks that had been deposited successively, and marks that had been deposited with a ten second interval in between depositions. Such an interval allows for the regeneration of secretions from the pores located on the ridges of the fingers. On fingermark depletions with no time interval between depositions, PD and Ind-Zn treated depletions successively (and comparatively) decreased in development intensity as the amount of residue diminished. Short time intervals in between successive depletions resulted in additional secretions from the pores intermittently occurring, the increased development of which was visualised by treatment with both PD and Ind-Zn. The changes in development intensity were seen with both techniques on the same split depletions in a series, comparably and proportionately. These results indicate that the components targeted by PD are contained in the material excreted by the friction ridge pores through its mirrored development with Ind-Zn. Repetition of the experiments on marks that only contained eccrine material showed good Ind-Zn development but poor results with PD. This indicates that there are other constituents contained in "natural" fingermarks that are required to be present for PD to be able to target constituents in the eccrine sweat. It may be that the required constituents in the natural residues are non-water soluble, and that these protect the eccrine constituents from solubilisation in the aqueous washes employed in the PD method. Further research is being undertaken to determine whether PD is targeting specific compounds in the pore secretions, or a mixture of compounds consisting of the eccrine material, epidermal lipids and sebaceous lipids typically present in latent fingermark residues.